PENERAPAN EKONOMI DIGITAL PEREMPUAN PENGRAJIN BORDIR DALAM RANGKA PENGUATAN EKONOMI RUMAH TANGGA DI NAGARI SINGGALANG TANAH DATAR - Yessy Andriani; Laksmi Dewi; Indrawari Indrawari (Jurnal Hilirisasi IPTEKS, 2020)
The embroidery craftsmen in Nagari Singgalang, Tanah Datar, have exquisite quality embroidery, but they do not significantly impact the craftsmen's income. This is because most of them are only wage earners. The wages they receive are not proportional to the processing they do. However, they do not have the bargaining power to increase wages due to many embroidery artisans. Low levels of education, lack of capital, and lack of knowledge about embroidery marketing are obstacles for them to develop. This activity aims to increase the productivity of artisans to become independent craftsmen (producers). The methods used are public participation and women participation in the economy through counseling, socialization, digital marketing training, and embroidery craftsmen. The extension is carried out to motivate them to be more productive while the practice is focused on digital marketing training to promote and market their products. The formation of an embroidery group is done so that they can work together and move forward together. This service is also complemented by providing embroidery materials and equipment to the assisted embroidery groups to start production and marketing themselves and not only as wage earners. The results of the activity resulted in four mukenah pieces with different variations and prices. The resulting product has been sold well so that the proceeds from the sale are used again to buy production materials, and part of it is distributed as profit. Thus this activity has a positive impact on the development of the embroidery business in Nagari Singgalang. In the future, this activity can become a pilot project for other groups to improve the embroidery craftsman family's welfare.